2014
DOI: 10.31686/ijier.vol2.iss12.288
|View full text |Cite
|
Sign up to set email alerts
|

Work Environment and its Influence on Productivity Levels among Extension Officers in the Ministry of Agriculture in Kenya

Abstract: From a broad perspective, a work environment can be defined as the location in which a task is performed. However, from an employment perspective, the work environment entails the physical geographical location of the job as well as its immediate surroundings (typically the tools and equipment required for the performance of the different tasks required for the job, work processes and procedures, quality of the air, noise level and any additional perks). As known, the work environment in an organization plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This finding is also in tandem with the studies of Abayomi and Ziska (2014) who in their study confirmed that there is a statistically significant relationship between promotion and satisfaction. (Mokaya et al, 2015;Danish and Usman, 2010;Yaseen, 2013;Mutiat andSikalieh, 2013 andVijayakumar andSubha, 2013). Also, this result is supported by the assertion of Abdullah and wan (2013), who established that when employees are well acknowledge in terms of promotion, their working capacity and job satisfaction of such staff will increase.…”
Section: Test Of Association Between Personal Characteristics Of Resp...mentioning
confidence: 99%
“…This finding is also in tandem with the studies of Abayomi and Ziska (2014) who in their study confirmed that there is a statistically significant relationship between promotion and satisfaction. (Mokaya et al, 2015;Danish and Usman, 2010;Yaseen, 2013;Mutiat andSikalieh, 2013 andVijayakumar andSubha, 2013). Also, this result is supported by the assertion of Abdullah and wan (2013), who established that when employees are well acknowledge in terms of promotion, their working capacity and job satisfaction of such staff will increase.…”
Section: Test Of Association Between Personal Characteristics Of Resp...mentioning
confidence: 99%
“…Customary local wisdom and culture, such as customary institutions, have the potential and strength to interact in the era of globalization by establishing economic mobility for the welfare of groups, individually or collectively, to develop new economic enterprises in the community. Agricultural development objectives are: (i) increase human resources for professional apparatus, independent farmers, and strong agricultural organizations and institutions, (ii) sustainable use of agricultural products, (iii) increase food security, (iv) increase product competitiveness, (v) rural community economic growth and (vi) develop agricultural development governance that is beneficial to farmers (Mutia & Sikalieh, 2014). Interactive participation is a type of stakeholder participation suitable for implementing agricultural development programs in the community (Gonsalves, 2005;Pretty, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The organization as the parent company must provide a comfortable and conducive work environment that can provoke employees to work productively. Mutia & Sikalieh (2014) reveal that the work environment in an organization can be a big determinant of the level of worker productivity. This opinion was supported by Desmonda (2016) who in his research found that the physical work environment consisting of office space, lighting, color, air, music, and noise level had a significant influence on employee productivity.…”
Section: Introductionmentioning
confidence: 99%